1961
DOI: 10.1055/s-0037-1621159
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Cardiac Output and ”Pulmonary Blood Volume” in Normal Man by External Recording of the Intracardiac Flow of 131I Labelled Albumin

Abstract: Summary1. The technique for the measurement of cardiac output by external recording of the intracardiac flow of 131I labelled human serum albumin has been extended to provide a measure of the mean circulation time from right to left heart and hence a new approach to the estimation of the pulmonary blood volume.2. Values for the basal cardiac output in normal subjects and its variations with age are in good agreement with the previously published data of other workers.3. The pulmonary blood volume in normal man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1962
1962
1963
1963

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The cardiac index in the youngest age-group was significantly higher than the rest of the series though whether this observation truly reflects the influence of age or whether it represents incomplete elimination of the influence of body size on the data is uncertain. The absence of change in cardiac index from 10 years upwards is of interest and should be contrasted with the data of Brandfonbrener, Landowne, and Shock (1955) and Lammerant, Veall, and De Visscher (1961) who, in a study of older age-groups, each observed a progressive fall in cardiac index as age increased. Stroke index, by contrast, appears to rise slightly over the age range studied though the change is not significant except between the youngest and oldest groups (Table II).…”
Section: Discussionmentioning
confidence: 88%
“…The cardiac index in the youngest age-group was significantly higher than the rest of the series though whether this observation truly reflects the influence of age or whether it represents incomplete elimination of the influence of body size on the data is uncertain. The absence of change in cardiac index from 10 years upwards is of interest and should be contrasted with the data of Brandfonbrener, Landowne, and Shock (1955) and Lammerant, Veall, and De Visscher (1961) who, in a study of older age-groups, each observed a progressive fall in cardiac index as age increased. Stroke index, by contrast, appears to rise slightly over the age range studied though the change is not significant except between the youngest and oldest groups (Table II).…”
Section: Discussionmentioning
confidence: 88%
“…The narrow angle collimator shown in Fig. 1b is now used routinely for cardiac output and related measurements with 131I-Iabelled albumin (LAMMERANT, VEALL and DE VISSCHER 1961). In these and other procedures the use of the well crystal has made it possible to reduce the tracer dose administered to the patient by a factor four and still have higher count rates than those achieved with the more conventional system.…”
Section: Clinical Applicationsmentioning
confidence: 99%